Ethics and social security reform - Schokkaert, Erik,Ed (Routledge, 2018)
This title was first published in 2001. Ethical considerations play a key role in both the theoretical and practical functioning of the welfare state. The contributors to this book examine these ethical issues, and demonstrate how value judgements must be integrated into any analysis of social security reform.